RISK MANAGEMENT THROUGH CORPORATE SOCIAL RESPONSIBILITY AS A WAY TO SUSTAINABILITY IN HOSPITALITY INDUSTRY - Arora, Gitika; Kalia, Yatisha; Arora, Sanjeev; Kaur, Gaganpreet (International Journal of Psychosocial Rehabilitation, 2020)
In the dynamic environment of growth and development, managing risk has become the biggest challenge for any company for their long term sustainability and growth. With the development of industry in India, companies are facing risk and becoming aware of being socially responsible which provides "insurance-like" protection (Godfrey, 2005; Friedman, 1953) against various types of risk. Corporate Social Responsibility is being used as a strategic tool for managing risk in business (Lenssen et al., 2007; Basu and Palazzo, 2008). This paper is based on an extensive review of literature in the field of managing risk with the help of CSR activities in the hospitality industry. The findings of the study show that CSR plays a vital role in controlling or mitigating various types of risk in the hospitality industry. The study has also proposed a framework that explains the use of CSR for managing risk.